EFL PRE-SERVICE TEACHERS’ SELF-EFFICACY BELIEFS DURING TEACHING PRACTICUM - Cania, Meta; Kusriandi, Wendi; Dwiniasih, Dwiniasih (Sanata Dharma University Yogyakarta, 2024)
The purpose of this study is to look into pre-service EFL teachers' self-efficacy beliefs about teaching English as they progress through their teaching practicum. The study's findings were gathered through a survey of 20 pre-service EFL teachers enrolled in the Faculty of Education at one of Cirebon's private universities. Teachers' Sense of Efficacy Scales of 24 questions were used to gather data, which evaluates pre-service teachers' self-efficacy on three subscales: student engagement, instructional strategy, and classroom management. The results were analyzed using descriptive statistics to determine which EFL pre-service teachers had the highest and lowest levels of self-efficacy. The study's findings revealed that their self-efficacy is at a medium level, and they are more effective in terms of instructional strategy. The study of self-efficacy regarding EFL students' practicum has significance for any institution involved in building higher-quality programs for future-generation teachers.